Talent Retention through Employee Engagement, Human Resource, Knowledge and Change Management: A Conceptual Framework - Kossyva, Dorothea; Theriou, Georgios; Aggelidis, Vassilis; Sarigiannidis, Lazaros (International Journal of Applied Research in Management and Economics, 2021)
This study examines talent retention in the Information and Communication Technology (ICT) sector by focusing on the relationships between human resource management (HRM), knowledge management (KM), change management (CM) and employee engagement. In this respect, a conceptual framework is proposed to understand the relationships between these constructs. The proposed framework highlights the importance of implementing specific talent retention practices in knowledge-intensive sectors like ICT, in order for employees to be engaged both with their work and their organization.